2024
DOI: 10.1039/d3dt04276f
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high photoelectric conversion efficiency and obvious carrier separation in photovoltaic ZnIn2X4 (X = S, Se, and Te) van der Waals heterostructures

Zheng Liang,
Yao-Zhong Liu,
Ze-Ting Gong
et al.

Abstract: The need of low carbon solar electricity production has become increasingly urgent for energy security and climate change mitigation. However, the bandgap and carrier separation critical requirements of high efficiency...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that the synergistic regulation strategy of dimensional reduction and heterogeneous structure construction can significantly enhance catalytic activity, which has important application potential in energy conversion, energy storage, environmental purification, and other fields. , Especially, two-dimensional band-staggered van der Waals (vdW) heterostructures, including type-II and direct Z-scheme, have attracted extensive attention due to their substantial specific surface area, exceptional photoelectric conversion performance, tunable electronic structure, and light absorption characteristics, , such as CuBiP 2 Se 6 /C 2 N and MoSSe/WSeTe . It is worth noting that although type-II heterostructure can effectively facilitate the separation of photogenerated electron–hole pairs to a certain extent, their oxidation and reduction ability is limited by the positioning of the material’s band edge. , In contrast, the direct Z-scheme heterostructure not only improves the separation efficiency of photogenerated hole–electron pairs owing to a unique electron–hole transfer mechanism but also augments the redox ability of photogenerated carriers at active sites within the heterojunction catalyst. , Therefore, the construction of a direct Z-scheme photocatalyst has become the pursuit of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the synergistic regulation strategy of dimensional reduction and heterogeneous structure construction can significantly enhance catalytic activity, which has important application potential in energy conversion, energy storage, environmental purification, and other fields. , Especially, two-dimensional band-staggered van der Waals (vdW) heterostructures, including type-II and direct Z-scheme, have attracted extensive attention due to their substantial specific surface area, exceptional photoelectric conversion performance, tunable electronic structure, and light absorption characteristics, , such as CuBiP 2 Se 6 /C 2 N and MoSSe/WSeTe . It is worth noting that although type-II heterostructure can effectively facilitate the separation of photogenerated electron–hole pairs to a certain extent, their oxidation and reduction ability is limited by the positioning of the material’s band edge. , In contrast, the direct Z-scheme heterostructure not only improves the separation efficiency of photogenerated hole–electron pairs owing to a unique electron–hole transfer mechanism but also augments the redox ability of photogenerated carriers at active sites within the heterojunction catalyst. , Therefore, the construction of a direct Z-scheme photocatalyst has become the pursuit of researchers.…”
Section: Introductionmentioning
confidence: 99%